Grammatical change origins, nature, outcomes - Jonas, Dianne; Whitman, John, 1954-; Garrett, Andrew (Oxford : Oxford University Press, 2012)
This text advances research on grammatical change and shows the breadth and liveliness of the field. International scholars report on the nature and outcomes of all aspects of syntactic change, including grammaticalization, variation, syntactic movement, determiner-phrase syntax, pronominal systems, case systems, and alignment.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Morphology; Linguistic change